Preface: Motivation, work performance and leadership: Factors affecting business productivity - Pelekais, Cira (REVISTA CIENTIFICA GLOBAL NEGOTIUM, 2022)
According to Bohórquez et al. (2020), in today’s world, organizations must make it a priority to keep human talent motivated, as it is considered the most important capital for its contribution to provide development and productivity. Emphasizing that, worldwide, companies are adopting changes according to market trends, however, few are those that implement new systems, exclusively for human talent, to make them feel motivated to perform the assigned activities, because their work is not valued or compensated, creating a labor dissatisfaction that minimizes the productivity of the organization.